Effect of Organizational Structure on Organizational Agility in Islamic Azad University Region 6 of Khuzestan (from the View of University Professors) - ghanbar amirnezhad; parastoo azhdari (توسعه اجتماعی, 2016)
Since the environmental changes on organizational many aspects has effected, organizations must use appropriate strategies to dynamically adapt to environmental changes to be able to itself survive. The organization is designed to agile form, has a unique organizational structure, which makes the act more effective in their processes. The main objective of this study is investigating the impact of organizational structure on organizational agility. Statistical society of research is Islamic Azad university’s professors in region 6 of khuzestan. Present research method based on the target is empirical, and based on the method of data collection is a descriptive research; also based on the relationship between variables is causal research, and specifically, it is based on structural equation modeling. In order to measure the research variables used questionnaire and methods of statistical analysis by spss and lisrel software. The results of the questionnaires analysis showed that organizational structure (and its dimensions) significant and negative effect on organizational agility.